2022
DOI: 10.1101/2022.01.08.22268953
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-PEG Antibodies Boosted in Humans by SARS-CoV-2 Lipid Nanoparticle mRNA Vaccine

Abstract: Humans commonly have low level antibodies to poly(ethylene) glycol (PEG) due to environmental exposure. Lipid nanoparticle mRNA vaccines for SARS-CoV-2 contain small amounts of PEG but it is not known if PEG antibodies are enhanced by vaccination and if there are any consequences. We studied plasma from 55 people receiving the Comirnaty (Pfizer-BioNTech) mRNA vaccine for PEG-specific antibodies. Anti-PEG IgG was commonly detected prior to vaccination and was boosted a mean of 1.78-fold (range 0.68 to 16.6) by … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 47 publications
5
24
2
Order By: Relevance
“…Moreover, serum from mRNA-1273 vaccine recipients was able to recognize components of both formulations in a prime-boost dependent manner. Importantly, similar outcomes to our findings have been recently described [37] . It remains to be explored whether the anti-PEG antibodies induced following vaccination are directed towards the backbone of the PEG molecule, or the methoxy group present in PEG from both formulations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, serum from mRNA-1273 vaccine recipients was able to recognize components of both formulations in a prime-boost dependent manner. Importantly, similar outcomes to our findings have been recently described [37] . It remains to be explored whether the anti-PEG antibodies induced following vaccination are directed towards the backbone of the PEG molecule, or the methoxy group present in PEG from both formulations.…”
Section: Discussionsupporting
confidence: 93%
“…First, the sample size of the side effect cohort did not allow us to confidently evaluate the relationship between PEG reactive antibodies and adverse reactions induced by vaccination. A recent report from Ju and colleagues [37] suggests that the elevated levels of vaccine-induced anti-PEG antibodies correlated with increased systemic reactogenicity after two vaccine doses. In addition, we did not detect a significant increase in anti-PEG antibodies in BNT162b2 recipients, which might be due to the limited number of subjects studied in our cohort.…”
Section: Discussionmentioning
confidence: 98%
“…However, studies have shown that healthy humans have pre-existing anti-PEG antibodies, which can affect the fate and utility of PEGylated nanomedicines. [25][26][27] Therefore, alternative strategies are needed to endow nanoparticles with stealth properties. Owing to the intrinsic biocompatibility and low immunogenicity of biomolecules, precoating nanoparticles with biomolecules (prior to their administration in the body/contact with blood) is emerging as a promising strategy for providing a protective coating on nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, two studies reported the rise of anti-PEG Abs in Spikevax-vaccinated people, 21,22 implying specific binding of these Abs to PEG in the vaccine. In earlier studies, anti-PEG Abs were shown to cause rapid loss of efficacy along with increased the risk of HSRs to PEGylated urate oxidase, 23,24 and in another example, 3 anaphylactic reactions in patients having very high pre-existing anti-PEG Abs led to early termination of a Phase II clinical trial with the PEGylated RNA aptamer, Pegnivacogin.…”
Section: Introductionmentioning
confidence: 99%
“…These anti-PEG Abs were also correlated with the levels of SARS-CoV-2 neutralizing Abs, taken as endpoint for vaccine efficacy, and relating the postvaccination anti-PEG Ab levels to the pre-vaccination values allowed us to investigate "bystander" anti-PEG immunogenicity, similar to that reported for Spikevax. 21,22…”
Section: Introductionmentioning
confidence: 99%